Accounting Competition Vol. 2.0 sebagai Wadah Optimalisasi Kreativitas Generasi Muda terhadap Perkembangan Akuntansi - Murapi, Ikang; Oki Astarini, Dewa Ayu; Sriwinarti, Ni Ketut; Septian, Defel; Khairunnisa (Insan Kreasi Media, 2023)
The Accounting Competition program is a form of community service which is an annual routine agenda carried out by lecturers and students of the Bumigora University accounting study program. In the second year of implementation, this activity was named ACTION VOL 2.0 at SMA/SMK/MA level throughout Lombok Island with the theme